Determinants of Indonesian Palm Oil Exports to Pakistan - Dewi Setiawati; Aris Soelistyo; Syamsul Hadi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2026)
This study aimed to analyze the impact of inflation, exchange rate, and production on Indonesia's palm oil exports to Pakistan. The analysis was conducted using the Error Correction Model (ECM), which enabled identification of both short- and long-term relationships among the variables. The tests carried out in this study included the Stationarity Test, Cointegration Test, and Classical Assumption Tests, which consisted of the Multicollinearity Test, Normality Test, Heteroscedasticity Test, and Autocorrelation Test. The data used were secondary data obtained from publications by Statistics Indonesia (BPS) and the World Bank, covering a period of 33 years, from 1991 to 2023. The results of the study indicated that in the long term, inflation and the exchange rate had positive but insignificant effects on exports, while production had a positive and significant effect. In the short term, inflation had a positive and significant impact, while the exchange rate and production remained positively related to exports, although their effects were not statistically significant on Indonesia's palm oil exports to Pakistan.